Significance of experts’ overall ratings for medical student competence in relation to history-taking - Troncon, Luiz Ernesto de Almeida (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Overall ratings (ORs) of competence, given by expert physi- cians, are increasingly used in clinical skills assessments. Nevertheless, the influence of specific components of competence on ORs is incompletely understood. The aim here was to investigate whether ORs for medical student history-taking competence are influenced by performance relating to communication skills, completeness of questioning and asking content- driven key questions. DESIGN AND SETTING: Descriptive, quantitative study at Faculdade de Medicina de Ribeirão Preto, Universidade de São Paulo. METHODS: Thirty-six medical students were examined in a 15-station high-stake objective structured clinical examination (OSCE). At four stations devoted to history-taking, examiners filled out checklists covering the components investigated and independently rated students’ overall performance using a five-point scale from 1 (poor) to 5 (excellent). Physician ratings were aggregated for each student. Nonparametric correlations were made between ORs. RESULTS: ORs presented significant correlations with checklist scores (Spearman’s rs = 0.38; p = 0.02) and OSCE general results (rs = 0.52; p < 0.001). Scores for “communication skills” tended to correlate with ORs (rs = 0.31), but without reaching significance (p = 0.06). Nei- ther the scores for “completeness” (rs = 0.26; p = 0.11) nor those for “asking key questions” (rs = 0.07; p = 0.60) correlated with ORs. CONCLUSIONS: Experts’ overall ratings for medi- cal student competence regarding history-taking is likely to encompass a particular dimension, since ratings were only weakly influenced by specific components of performance.